Remittances, Social Change, and Rural Transformation: A Case Study of Banyusri Village, Boyolali - Rindirindi, Bagas; Jayanto, Pasca Dwi (The Indonesian Journal of Planning and Development, 2026)
Rural-urban migration and remittances play a central role in shaping socio-economic restructuring in agrarian villages facing structural constraints, including Banyusri Village. Migration has emerged as an adaptive livelihood strategy in response to land scarcity, declining agricultural productivity, and persistent rural-urban income disparities, while remittances function as a critical source of household and community support. Using a qualitative case study approach based on in-depth interviews, participant observation, and document analysis, this study examines migration patterns, forms and uses of remittances, and their impacts on socio-economic transformation in Banyusri. The findings show that migration is driven by structural rural pressures and reinforced by intergenerational migrant networks that facilitate, normalize, and perpetuate mobility over time. Remittances enhance household economic resilience by supporting consumption, education, healthcare, savings, and productive investment in high-value agricultural sectors. At the community level, migrant contributions strengthen religious, cultural, and social infrastructure, reinforcing collective participation and social cohesion. At the village level, remittances stimulate economic regeneration by generating employment opportunities, circulating capital, and expanding collective assets; however, they also produce emerging inequalities through differentiated consumption patterns, the rise of “successful migrant” social strata, and potential household dependency. Overall, the study demonstrates that remittances operate not only as financial transfers but also as transformative social resources that reshape household strategies, community relations, and broader rural development pathways. By analyzing how remittances are mobilized, utilized, and socially interpreted, this research contributes to wider debates on migration, rural livelihoods, and the dynamics of rural transformation in Indonesia.